2017
DOI: 10.1130/ges01386.1
|View full text |Cite
|
Sign up to set email alerts
|

Untangling tectonic slip from the potentially misleading effects of landform geometry

Abstract: We present a new three-dimensional (3D) approach to the analysis of fault scarps using high-resolution elevation models. Advances in topographic measurement techniques [e.g., lidar (light detection and ranging) and photogrammetric techniques] have allowed extensive measurement of single earthquake and cumulative scarps to draw conclusions about along-strike slip variation and fault slip history. The resulting slip distributions are almost always variable and noisy, but the cause is often unclear. We first pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 54 publications
1
34
1
Order By: Relevance
“…Surveys of the present‐day streambeds showed that the post‐depositional tilt of the fitted surfaces is negligible. The geometrical error introduced by the landform geometry in the sense of Mackenzie and Elliott () also does not affect our results significantly beyond the noted 10% uncertainties.…”
Section: Methodssupporting
confidence: 46%
“…Surveys of the present‐day streambeds showed that the post‐depositional tilt of the fitted surfaces is negligible. The geometrical error introduced by the landform geometry in the sense of Mackenzie and Elliott () also does not affect our results significantly beyond the noted 10% uncertainties.…”
Section: Methodssupporting
confidence: 46%
“…As no fault plane slip direction indicators were found, we assume that the faults are purely normal (Chorowicz & Sorlien, ; Jackson & Blenkinsop, ). Under this assumption the scarp height may be used to represent the surface displacement (Morley, ), except where the scarp trend varies considerably from the average trend (Mackenzie & Elliott, ). Relative to the fault length, the average vertical surface displacement (∼14 m) is greater than would be expected by a single earthquake event (∼6 m; Scholz, ), but the maximum surface displacement (∼28 m) is significantly less than expected for the total displacement (∼1,000 m; Kim & Sanderson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several sources of errors are revealed. The first is related to a possible incorrect identification of the two marker sections to be paired (e.g., Mackenzie & Elliott, ; Scharer et al, ; Zielke et al, ). The expertise of the user is here fundamental and irreplaceable.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the explosion of high‐resolution topographic data, especially Lidar that allows the measurement of the bare Earth surface at ≤1 m resolution (e.g., Arrowsmith & Zielke, ; Bevis et al, ; De Pascale et al, ; Frankel et al, ; Haddad et al, ; Lin et al, ; Meigs, ; Zielke et al, ; Zielke et al, ), has motivated the development of new, automatized approaches to remotely measure fault slips in the topographic data. These approaches, so far, use an overall measure of the topography (Billant et al, ), planar surfaces (Mackenzie & Elliott, ), or linear geomorphic features (Haddon et al, ; Zielke et al, ; Zielke & Arrowsmith, ) as recorders and markers of the fault displacements. In particular, Zielke and Arrowsmith () and Zielke et al () have developed a Matlab code, LaDiCaoz (updated version, LaDiCaoz_v2, released by Haddon et al, ), to semiautomatically measure fault offsets across ubiquitous linear geomorphic features such as stream channels and terrace risers.…”
Section: Introductionmentioning
confidence: 99%